Preparation of CdS-PbS solid solutions thin films by modifying of the cadmium sulfide film surface when it exposed to an aqueous solution of lead salt - N. A. Forostyanaya; A. O. Polepishina; V. F. Markov; L. N. Maskaeva (Chimica Techno Acta)
The composition, structure, and morphology of multiphase semiconductor as-deposited CdS films and CdS incubated in a lead acetate solution were studied. Compositions examined by electron microscopy and by the Raman scattering. For the first time it was present the formation of a solution at the interface «metal chalcogenide thin film - water solution». Summarizing the results, we can conclude that exposure precipitated films of cadmium sulfide in aqueous salt solution of lead ensures PbS part of the film with the formation of thin-film songs CdS-PbS, including solid solutions substitution Pb1-xCdxS. With subsequent heat treatment of layers when 423 K increases the content of lead sulfide in the solid solution.